The NEW school rules : 6 vital practices for thriving and responsive schools - Kim, Anthony; Gonzales-Black, Alexis; Lai, Kawai (Thousand Oaks : Corwin, a SAGE company, 2018)
'This book is for every leader who wants to instigate change and create environments of growth, excitement, and passion. This book offers many techniques to help move from a top-down approach to management to a new style of'responsive organization' based on flexible roles, shared authority, and continuous learning and change. These new models of leadership and organizational design apply closely to even larger systems, including the schools and districts the authors work with every day. As they integrated these concepts and techniques with school leaders, the results have been tangible and effective in dozens of districts where we've introduced key practices'--
Planning: plan for change, not perfection -- Teaming : build trust and allow authority to spread -- Managing roles : define the work before you define the people -- Decision-making : aim for'safe enough to try' over'consensus' -- Sharing information : harness the flow and let information go -- The learning organization : schools grow when people grow.
Includes bibliographical references and index.
Keywords: Educational leadership -- United States; School management and organization -- United States